(untitled) (Studia Prawnicze / The Legal Studies, 2014)
Celem niniejszego opracowania jest ukazanie w kontekście systemowym istoty współczesnego normatywnego postrzegania własności w rolnictwie i przypisywanych temu prawu funkcji, a także przemian w ujmowaniu tej formy własności. Z tego też względu Autorzy, analizując prawo własności środków produkcji rolnej, zwracają uwagę nie tylko na zmiany w normatywnym ujęciu własności rolniczej, ale również podejmują próbę ukazania zmieniającego się kontekstu społecznego, politycznego i gospodarczego rzutującego na postrzeganie tej instytucji prawa. W tym względzie szczególne znaczenie przypisano zmianom modelu legislacyjnego dotyczącego sektora rolnego wynikającym z transformacji ustrojowej, jaka nastąpiła w Polsce na przełomie lat 80/90-tych XX wieku oraz będących następstwem przystąpienia Polski do Unii Europejskiej co wiązało się z włączeniem rodzimego sektora rolnego w ramy Wspólnej Polityki Rolnej (WPR) In the article, the Authors attempt to systematically formulate “property”, from the point of view of both – Polish and EU legislation. They highlight various understandings of property and point out, how complicated the evolution of this law aspect has been. The point of reference in the conducted analysis is the assumption that property is one of the most important elements of the legal order. It is also perceived as a pillar of social and economic system. At the same time, property, and more precisely – its juridical concept assumed by a legislator as a factor shaping not only the content of property right but also determining its allowable forms, constitutes a fundamental instrument used by a country to influence its social and economic reality. As a reference to the Polish law, the Authors presented understandings of property that result from the constitution and civil law and pointed out fundamental differences between them. They highlighted also the fact that the constitutional concept of property is normatively superior to the other concept, what is reflected by the fact that property, formulated in the Constitution as an elementary right, determines the requirements concerning statutory under-standing of property. According to the principles of EU legislation, property is also perceived as an elementary right, but, as in the Polish law, it does not constitute an absolute (unlimited) right. It is though indicated that public interest in the broad sense of the term may constitute a legal prerequisite for interference in owner’s entitlements.